All problems can never be solved - Wouters, Jozef; Matthé, Pol.; Tacq, Filiep; Wendler, Reinhard (Perk : Mennomichieljozef vzw, 2014)
Asked to make a work of art in a modernist social housing complex called Cité Modèle (Model District) in Brussels, the artist and scenographer Jozef Wouters founded a temporary architecture office in one of the apartments. Over time, Bureau Des Architectes became a place where professional architects, artists and local residents gathered to solve problems, express desires or propose discussions. Restricting all participants only to work with scale models in order not to be distracted by reality, the project accumulated in an exhibition that questions the problem-solving nature of architecture by means of 46 scale models for possible and impossible desires. Two years after, Wouters joined forces with visual artist Pol Matthé to make this book. Using the three-dimensional software developed for architects to visualize the future, they made a replica of the past exhibition based on pictures and their own memory. While virtually rebuilding the past, they also rearranged, reimagined and reframed it. The result is a book that serves as a scale model of a project, articulating its desires and propositions more than documenting it.
boek
Keywords: Wouters, Jozef; Matthé, Pol; Architecture -- Belgium -- Brussels -- Catalogs; Architecture; Belgium -- Brussels; Wouters, Jozef -- 1986-; Sozialer Wohnungsbau; Architekturmodell; Brüssel